Low temperature sinterable conductive copper paste, method of making and electronic device

CN122370037BActive Publication Date: 2026-11-03SHANGHAI SILVER PASTE SCI & TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610830452.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-10
Publication Date
2026-11-03
Estimated Expiration
2046-06-10

AI Technical Summary

Technical Problem

Copper powder is prone to oxidation during storage and processing, which leads to a decrease in conductivity. In addition, the traditional copper paste has a high sintering temperature, making it difficult to adapt to flexible substrates.

Method used

A three-dimensional interpenetrating conductive network was formed by coating copper powder with graphene, where the defect density of the graphene shell increases from the inside out, combined with nitrogen-containing composite resin and reducing agent, and prepared by low-temperature fluidized bed chemical vapor deposition process.

Benefits of technology

Low-temperature sintering was achieved, which improved the stability and adhesion of the copper paste, solved the problem of copper powder oxidation, and adapted to flexible substrates to form a continuous conductive network, thereby improving conductivity and oxidation resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application provides a low-temperature sintering conductive copper paste, a preparation method and an electronic device. The conductive copper paste comprises graphene-coated copper powder, nitrogen-containing composite resin, a reducing aid and an organic solvent. The graphene-coated copper powder comprises a copper core and a graphene shell layer coated outside the copper core. The defect density of the graphene shell layer increases from inside to outside. The graphene-coated copper powder can be applied to a flexible substrate and can form a three-dimensional interpenetrating graphene continuous conductive network under a low-temperature sintering environment. The preparation method comprises a three-stage low-temperature fluidized bed chemical vapor deposition process for preparing the graphene-coated copper powder. The preparation method is simple and has strong operability. The electronic device is prepared by using the conductive copper paste, so that the signal transmission of the electronic device is stable and reliable, and the overall performance of the electronic device is good and the service life is long.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of semiconductor devices, and in particular to a low-temperature sintering conductive copper paste, its preparation method, and electronic devices. Background Technology

[0002] Conductive copper paste is a core electronic material that is replacing traditional silver paste due to its significant cost advantage. However, copper powder is highly susceptible to oxidation during storage, processing, and sintering, forming insulating copper oxide or cuprous oxide, which leads to a sharp decline in conductivity.

[0003] To address the issue of copper powder's susceptibility to oxidation, two conventional solutions exist: 1. Physical blending of copper powder and graphene. While this approach can improve oxidation resistance to some extent, graphene is prone to agglomeration and has poor dispersibility, making it difficult to form a continuous protective structure. 2. Coating the surface of copper powder with continuous, dense graphene to create a structure where copper powder is coated with continuous, dense graphene. Although this method offers excellent oxidation resistance, the dense graphene shell hinders the formation of sintering necks between copper particles, resulting in a porous film and reduced conductivity.

[0004] Furthermore, the traditional copper paste sintering temperature is generally higher than 300℃, making it difficult to adapt to flexible substrates. Graphene has a strong surface inertness and poor interfacial compatibility with organic resin systems, which can easily lead to defects such as filler sedimentation, high interfacial resistance, and insufficient adhesion. Summary of the Invention

[0005] In view of this, the purpose of the present invention is to provide a conductive copper paste suitable for flexible substrates and capable of low-temperature sintering, and a method for preparing the same.

[0006] The first objective of this invention is to provide a low-temperature sintering conductive copper paste, comprising graphene-coated copper powder, nitrogen-containing composite resin, reducing agent, and organic solvent. The graphene-coated copper powder includes a copper core and a graphene shell covering the copper core, wherein the defect density of the graphene shell increases from the inside to the outside.

[0007] Coating copper powder with graphene, using copper powder as the core and a graphene shell as the outer shell, protects the copper powder from oxidation. The formulation also includes reducing agents to inhibit copper core oxidation, preventing a sharp decline in conductivity due to copper powder oxidation. The graphene shell in this application is not a dense structure but contains defect sites. During sintering, cracked graphene shells can undergo in-situ overlapping, defect reconstruction, and self-repair under the residual heat of sintering. The defect sites in the graphene shell can form coordination bonds and hydrogen bonds with the nitrogen-containing composite resin. Ultimately, a three-dimensional interpenetrating graphene continuous conductive network is formed outside the metallurgical conductive pathways between copper particles, constructing a double continuous conductive pathway. This solves the industry problems of filler agglomeration, poor dispersion, and poor interfacial compatibility caused by the inertness of the graphene surface, improving the stability of the copper paste and the adhesion of the film layer. Furthermore, in this invention, the graphene shell and copper powder are integrated into one piece. Compared with traditional copper paste, the conductive copper paste in this invention has a lower sintering temperature, which can solve the technical problem that the sintering temperature of traditional copper paste is too high and difficult to adapt to flexible substrates in the prior art.

[0008] Furthermore, by mass percentage, the graphene-coated copper powder comprises 72wt%–86wt%, the nitrogen-containing composite resin comprises 4wt%–12wt%, the reducing agent comprises 0.3wt%–2.5wt%, and the balance is organic solvent.

[0009] In this invention, the amount of graphene-coated copper powder added is controlled at 72wt%–86wt%, and the amount of nitrogen-containing composite resin added is controlled at 4wt%–12wt%. If the amount of graphene-coated copper powder added is higher than 86wt%, it easily leads to excessive viscosity of the copper paste, poor dispersibility, reduced film density and adhesion, and deterioration of conductivity and reliability. If the amount of graphene-coated copper powder added is lower than 72wt%, there is insufficient conductive filler, making it difficult to form a continuous conductive network, and the resistivity increases significantly. If the amount of nitrogen-containing composite resin added is higher than 12wt%, it will result in excessive organic residue after sintering, hindering the construction of conductive pathways, leading to increased resistivity and poor high-temperature and high-humidity stability. If the amount of nitrogen-containing composite resin added is lower than 4wt%, it cannot fully wet the graphene shell, resulting in insufficient dispersion stability of the copper paste and insufficient film adhesion, and problems such as sedimentation and film peeling are likely to occur.

[0010] Further, by mass percentage, it includes: organic solvent balance of 9.7wt% to 21.57wt%.

[0011] Furthermore, the graphene-coated copper powder comprises a low-defect inner layer of graphene, a gradient transition layer of graphene, and a high-defect outer layer of graphene sequentially coated on the copper core.

[0012] Among them, the low-defect inner graphene is in direct contact with the copper core and covers the outside of the copper core, isolating the copper core from air and water vapor, thus isolating the copper core from the outside air and preventing the copper core from oxidizing; during the growth of the low-defect inner graphene, the copper atoms on the surface of the copper core bond in situ with the carbon atoms of the graphene to form a Cu-C and Cu-OC covalent bond interface transition layer, which can ensure the stability of the core-shell structure. The gradient transition layer of graphene serves as a bridge between the low-defect inner graphene and the high-defect outer graphene. The number of defect sites is between that of the low-defect inner graphene and the high-defect outer graphene, causing the defect density of the copper powder coated with graphene to increase from the inside to the outside, thus avoiding abrupt changes in interfacial stress. Conversely, without the gradient transition layer of graphene, the low-defect inner graphene and the high-defect outer graphene are directly connected. During sintering, cracks will be generated at the interface due to abrupt changes in interfacial stress, leading to debonding between the two graphene layers. This results in a structure where the low-defect inner graphene is exposed, making it difficult to form a sintering neck. The outer graphene layer with the highest defect density has the most defect sites, which play a role in forming coordination bonds and hydrogen bonds with nitrogen-containing composite resins. Ultimately, in addition to the metallurgical conductive pathways between copper particles, a three-dimensional interpenetrating graphene continuous conductive network is formed, constructing a double continuous conductive pathway. Only the outer graphene layer with the highest defect density undergoes local, moderate, and orderly cracking, while the inner low-defect dense graphene shell does not participate in cracking and still acts as a continuous anti-oxidation barrier, physically isolating oxygen and water vapor from contact with the copper core, thus inhibiting oxidation at its source.

[0013] Specifically, the low-defect inner layer graphene exhibits Ig in Raman spectroscopy. D / I G The ratio is close to 0; Specifically, the high-defect outer graphene in Raman spectroscopy exhibits Ig D / I G The ratio is greater than 1, the defect density is high, and there are a large number of edge sites, vacancies and N-doped sites, making it easy to crack, easy to overlap and easy to coordinate with resin.

[0014] Specifically, the gradient transition layer graphene in Raman spectroscopy exhibits Ig D / I G The ratio is greater than 0 and less than 1.

[0015] More specifically, low-defect inner-layer graphene I D / I G With a thickness of approximately 0.1 to 0.5, the graphene structure in this layer is intact and has high crystal integrity, which can form a dense antioxidant barrier on the surface of the copper core.

[0016] More specifically, gradient transition layer graphene I D / I GThe defect count is approximately 0.6 to 0.9, which is higher than the low-defect inner layer graphene, thus paving the way for the high-defect outer layer. Furthermore, the high-defect outer graphene contains defective active sites, which include polar active groups.

[0017] When the high-defect outer graphene is sintered at low temperatures of 180℃ to 230℃, it undergoes controlled and orderly cracking due to the stress generated by the melting of the nitrogen-containing composite resin and the evaporation of the solvent. The local cracking sites of the high-defect outer graphene are limited to a very small area, resulting in the exposure of a small portion of the copper cores. This allows for metallurgical bonding between the copper core particles. Therefore, compared to existing technologies, the copper cores of this invention are only exposed in very small numbers during the sintering process. Since the exposure only occurs at the defect cracks of the high-defect outer graphene, the exposed area is small, uniformly distributed, and does not involve large-area peeling. Furthermore, it only occurs at the sintering neck. The process is extremely short-lived. Once a metallurgical bond forms between the copper particles, the exposed area is immediately covered by the sintering neck and graphene fragments, eliminating the possibility of continuous exposure. Furthermore, during sintering, the reducing agent decomposes simultaneously and releases a reducing atmosphere, instantly reducing the exposed trace amounts of copper at the interface. This rapidly eliminates any trace amounts of copper oxide, ensuring the copper core remains in a metallic state. The outer graphene layer, after cracking, does not detach or leak but instead, driven by residual heat from sintering, reassembles and self-repairs in situ, quickly reforming the structure that encapsulates the copper core, further shortening the potential exposure time of the copper core. The fragments of the highly defective outer graphene layer, after cracking during sintering, can reassemble, reconstruct, and self-repair in situ, forming a three-dimensional continuous conductive network with the nitrogen-containing composite resin.

[0018] Specifically, the polar active groups include one or more of pyridine nitrogen, hydroxyl, and carboxyl groups, which can form coordination bonds and hydrogen bonds with nitrogen-containing composite resins. This not only inhibits the agglomeration of graphene-coated copper powder and makes it uniformly dispersed in conductive copper paste, but also significantly enhances the interfacial bonding force between graphene-coated copper powder and nitrogen-containing composite resins.

[0019] Furthermore, the diameter of the copper core ranges from 0.7 to 0.9 μm, and the median diameter is 0.8 μm. This ensures that the high-defect outer graphene can still cover the copper core after in-situ overlapping and self-healing, avoiding the situation where some copper cores are exposed and cannot be covered due to excessive differences in the particle size of the copper cores.

[0020] Furthermore, the graphene-coated copper powder shell consists of 1 to 4 layers of graphene.

[0021] Specifically, when the graphene-coated copper powder shell is one layer, the outer layer of the copper core is mainly low-defect inner graphene, which achieves initial dense coating of the copper core and provides basic antioxidant capacity. Specifically, when the graphene-coated copper powder shell has two layers, a low-defect inner layer of graphene and a gradient transition layer of graphene are sequentially attached to the outside of the copper core. Specifically, when the graphene-coated copper powder shell has three layers, the copper core is sequentially attached with a low-defect inner layer of graphene, a gradient transition layer of graphene, and a high-defect outer layer of graphene. Specifically, when the graphene-coated copper powder shell has four layers, the copper core is sequentially attached with a low-defect inner layer of graphene, a gradient transition layer of graphene, a high-defect outer layer of graphene, and another high-defect outer layer of graphene. The double-layer superimposed high-defect outer layer of graphene is rich in active sites and polar defects, which enhances the interfacial bonding with nitrogen-containing composite resin and achieves controllable cracking-in-situ bonding-self-repair during sintering.

[0022] Furthermore, the sum of the thicknesses of the low-defect inner graphene layer, the gradient transition layer graphene, and the high-defect outer graphene layer is 0.8 nm to 3.5 nm.

[0023] If the total thickness is less than 0.8 nm, the graphene coating is discontinuous and the density is insufficient, which cannot effectively block oxygen and significantly reduces the antioxidant performance. If it exceeds 3.5 nm, the graphene layer is too thick, which hinders the formation of metallurgical bonding between copper particles during low-temperature sintering, resulting in discontinuous conductive paths, increased resistivity and reduced film density.

[0024] Specifically, the sum of the thicknesses of the low-defect inner graphene layer, the gradient transition layer graphene, and the high-defect outer graphene layer is within a range formed by any one or any two of the following values: 0.8 nm, 0.9 nm, 1.0 nm, 1.1 nm, 1.2 nm, 1.3 nm, 1.4 nm, 1.5 nm, 1.6 nm, 1.7 nm, 1.8 nm, 1.9 nm, 2.0 nm, 2.1 nm, 2.2 nm, 2.3 nm, 2.4 nm, 2.5 nm, 2.6 nm, 2.7 nm, 2.8 nm, 2.9 nm, 3.0 nm, 3.1 nm, 3.2 nm, 3.3 nm, 3.4 nm, and 3.5 nm.

[0025] Furthermore, the copper core coating coverage rate is 92% to 98%. If the coverage rate is less than 92%, the exposed surface area of ​​the copper core is too large, which makes it easy to oxidize before or in the early stage of sintering, resulting in a decrease in conductivity and stability. If it is higher than 98%, it is almost completely coated. Although the oxidation resistance is excellent, it will seriously hinder the direct contact between copper cores, resulting in the inability to form an effective sintering neck, thus losing the metallurgical bonding ability.

[0026] In this invention, the copper core coating coverage rate refers to the percentage of the area of ​​the copper core surface covered by a continuous and complete graphene-coated copper powder shell layer to the total specific surface area of ​​the copper core.

[0027] Specifically, the copper core coverage rate is a range formed by any one or any two of the following values: 92%, 93%, 94%, 95%, 96%, 97%, and 98%.

[0028] Furthermore, the nitrogen-containing composite resin is selected from one or more of the following: nitrogen-containing epoxy-modified acrylic resin, amide-modified epoxy resin, pyridine-functionalized acrylic resin, tertiary amine-modified phenolic resin, polyamide-imide-modified epoxy resin, and nitrogen-doped polyurethane resin.

[0029] Nitrogen-containing composite resins can strongly coordinate with the active groups such as pyridine nitrogen, hydroxyl, and carboxyl groups of the high-defect outer layer of graphene, inhibiting the shedding of the graphene-coated copper powder shell during storage and sintering. Simultaneously, the polar groups contained in the resins can significantly improve the dispersion stability of the copper paste, reduce the tendency for particle aggregation, and ensure good leveling and formability of the copper paste during printing.

[0030] Furthermore, the organic solvent is a high-boiling-point solvent, which provides a suitable evaporation rate for the copper paste, avoiding defects such as pinholes and cracks in the copper paste film caused by excessively rapid solvent evaporation, while also preventing excessively slow evaporation from affecting production efficiency.

[0031] Specifically, the organic solvent includes one or more of the following: terpineol, ethylene glycol monobutyl ether, diethylene glycol monobutyl ether, diethylene glycol ethyl ether acetate, ethylene glycol monobutyl ether acetate, propylene glycol methyl ether acetate, dipropylene glycol methyl ether, tributyl citrate, and dioctyl adipate. Furthermore, the reducing agent comprises two or more of hypophosphite, ascorbic acid derivatives, polyols, and organic amines.

[0032] A second objective of this invention is to provide a method for preparing low-temperature sintered conductive copper paste, comprising: preparing graphene-coated copper powder; wherein the graphene-coated copper powder is prepared by a three-stage low-temperature fluidized bed chemical vapor deposition process. The three-stage low-temperature fluidized bed chemical vapor deposition process includes a first stage, a second stage, and a third stage; In the first stage, low-defect inner-layer graphene was grown at 550℃~600℃. In the second stage, a gradient transition layer of graphene was grown at 500℃ to 550℃. In the third stage, high-defect outer layer graphene is grown by nitrogen doping at 450℃~500℃.

[0033] By employing a three-stage low-temperature fluidized bed chemical vapor deposition process, the defect density state during graphene growth can be controlled by adjusting the temperature, thereby achieving a gradient coating structure from low-defect inner graphene to high-defect nitrogen-doped outer graphene. The preparation method is simple and highly operable.

[0034] Furthermore, during the preparation of graphene-coated copper powder using a three-stage low-temperature fluidized bed chemical vapor deposition process, trace amounts of natural oxide layers on the copper powder surface, oxygen-containing active groups generated from carbon source decomposition, and trace amounts of oxygen-containing impurities in the gas phase form an in-situ Cu-OC bonded interfacial transition structure between the copper substrate and the graphene shell under interfacial reaction conditions of 450℃~600℃. This structure is not a free copper oxide phase, but a composite interfacial layer of Cu, O, and C bonded by covalent and coordinate bonds, which together with the Cu-C interface constitutes a two-component internal interface. The presence of oxygen can significantly enhance the interfacial bonding strength between the copper core and graphene, inhibit coating layer detachment, and simultaneously act as an interfacial transition layer to block external oxygen diffusion to the copper core, improving overall oxidation resistance. In the subsequent low-temperature sintering process, the reducing agent can controllably reduce the trace oxide components at the interface, avoiding the formation of insulating copper oxide and ensuring interfacial conductivity and structural stability.

[0035] Specifically, it also includes a copper powder pretreatment step: selecting spherical copper powder with a particle size of 0.7 to 0.9 μm, acid washing with dilute hydrochloric acid, washing with deionized water and ethanol, and vacuum drying to remove the surface oxide layer and impurities.

[0036] Specifically, copper powder plasma activation: under an argon atmosphere, with a power of 80W to 200W, activation for 10 to 30 minutes to increase the density of surface active sites.

[0037] Furthermore, the first stage also includes: low concentration carbon source, Ar / H2 atmosphere, growth for 5 min to 15 min, forming low-defect inner layer graphene; The second stage also includes: increasing the carbon source concentration, introducing trace amounts of water vapor or CO2, growing for 3 to 8 minutes, gradually increasing the defect density, and forming a gradient transition layer of graphene. By controlling the temperature and carbon source concentration and introducing trace amounts of water vapor or CO2, lattice defects can be introduced in a controlled manner, so that the defect density increases from the inside to the outside, avoiding abrupt changes in interface stress. The defects in the gradient transition layer graphene are mainly topological and single-vacancy defects, which not only maintain the structural strength, but also provide transition sites for the growth of high-defect outer graphene, assist in the transfer of reduction, inhibit excessive oxidation of the interface, and synergistically construct the Cu-OC composite interface transition layer, strengthen the interface bonding force, and improve the resistance to damp heat and aging.

[0038] The third stage also includes: a high-concentration carbon source, a trace amount of NH3 atmosphere, growth for 5 min to 12 min, to form a high-defect outer layer of graphene rich in pyridine nitrogen, hydroxyl groups, and carboxyl groups.

[0039] The carbon source is selected from one or more combinations of methane, ethane, propane, ethylene, ethanol, isopropanol, acetone, ethyl acetate, and toluene; preferably, an oxygen-containing carbon source such as ethanol, acetone, or ethyl acetate is used, which can provide some oxygen-containing active species during the pyrolysis process, which is beneficial for the in-situ formation of a Cu-OC composite interface transition layer at the copper-graphene interface.

[0040] In the third stage of high-defect outer layer graphene growth, a trace amount of ammonia gas is introduced. The ammonia gas is decomposed at high temperature and nitrogen doped into the graphene. Nitrogen atoms preferentially occupy the graphene edges and defect sites, forming a large number of pyridine nitrogen structures, which significantly increases the surface polarity and the number of active sites. At the same time, nitrogen doping induces graphene lattice distortion, further increasing the defect density and realizing the construction of high-defect outer layer.

[0041] In the third stage, the supply of water vapor or CO2 was suspended because if water vapor or CO2 were to continue to be supplied, it would weaken the coordination of pyridine nitrogen. Too many defects would lead to instability in the graphene-coated copper powder shell structure, which would reduce conductivity.

[0042] A third objective of this invention is to provide an electronic device comprising a flexible substrate coated with a flexible film layer, the flexible film layer being formed by sintering a low-temperature sintered conductive copper paste as described in any one of the preceding claims, or by sintering a low-temperature sintered conductive copper paste prepared by the method described in any one of the preceding claims.

[0043] The flexible substrate of the electronic device is coated with a flexible film layer made of low-temperature sintered conductive copper paste provided by the present invention. It has good flexibility. Even when the flexible substrate is deformed, the formed double continuous conductive network is not easy to break, which makes the signal transmission of the electronic device stable and reliable, and helps to improve the overall performance and service life of the electronic device.

[0044] Furthermore, the volume resistivity of the flexible film layer is ≤6.5×10⁻⁶. -6 Ω·cm, resistivity drift rate <3% after aging at 85℃ and 85% relative humidity for 500h.

[0045] Specifically, the electronic devices include flexible circuit boards, RFID antennas, photovoltaic electrodes, semiconductor packages, and thick-film integrated circuits.

[0046] The beneficial effects of this invention are as follows: This invention provides a low-temperature sintering conductive copper paste, comprising a copper core and a graphene shell with increasing defect density from the inside to the outside, using graphene-coated copper powder. This overcomes the technical bottleneck of traditional dense shell coatings hindering sintering. During sintering, metallurgical conductive pathways are formed between copper particles, and the surface defect sites of the graphene-coated copper powder react with nitrogen-containing composite resin, undergoing a controllable structural evolution of controlled cracking, in-situ bonding, and self-repair. This constructs a dual-interface synergistic system of Cu-C / Cu-OC bonded inner interface and graphene-resin coordination outer interface, forming a three-dimensional interpenetrating continuous conductive graphene network. This results in good interfacial compatibility and dispersion of the conductive copper paste, and a stable sintered film.

[0047] (1) In this invention, the graphene shell with defect density increasing from the inside to the outside and copper powder are integrated into one. Compared with traditional copper paste, the conductive copper paste in this invention has a lower sintering temperature, which can solve the technical problem that the sintering temperature of traditional copper paste is too high and difficult to adapt to flexible substrates in the prior art.

[0048] (2) This invention provides a method for preparing low-temperature sintered conductive copper paste. Through a three-stage low-temperature fluidized bed chemical vapor deposition process, the defect density state during the graphene growth process is controlled by adjusting the temperature, thereby achieving a gradient coating structure from low-defect graphene in the inner layer to high-defect nitrogen-doped graphene in the outer layer. The preparation method is simple and highly operable.

[0049] (3) The present invention provides an electronic device, wherein a flexible film layer prepared by low-temperature sintering conductive copper paste provided by the present invention is attached to the flexible substrate of the electronic device. It has good flexibility. Even when the flexible substrate is deformed, the double continuous conductive network formed is not easy to break, which makes the signal transmission of the electronic device stable and reliable, and helps to improve the overall performance and service life of the electronic device. Detailed Implementation

[0050] Specific embodiments of the present invention will be described in detail below. It should be understood that the following detailed description is for illustrative purposes only, and obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the description of the present invention, all other embodiments obtained by those skilled in the art without inventive effort are within the scope of protection of the present invention.

[0051] In these embodiments, to demonstrate and verify the technical effects of the present invention, all embodiments adopt the following uniform conditions: S1. Copper powder pretreatment: Spherical copper powder with a particle size of 0.8μm (D50, distribution 0.7~0.9μm) (model: n-MP-Cu-S-800, supplier: Anhui Superlattice New Material Technology Co., Ltd., the same below) was selected, and it was placed in dilute hydrochloric acid (model: SEMI-G4, supplier: Zhongjuxin Technology Co., Ltd.) for acid washing, followed by deionized water (model: UP-182 electronic grade ultrapure water, supplier: Kunshan Qiancheng Environmental Protection Technology Co., Ltd., the same below) washing, and then anhydrous ethanol (model: EL-UP4N, electronic high-purity ethanol supplier: Jiangyin Kairui Chemical Technology Co., Ltd., the same below) washing. Then it was placed in a vacuum drying oven and dried at 60℃ and vacuum degree -0.095MPa for 4h to remove the surface oxide layer.

[0052] S2. Plasma activation: The pretreated copper powder is placed in a plasma activation device, and argon gas (model: Ar-5.0, supplier: Linde (China) Investment Co., Ltd., the same below) is introduced as a protective atmosphere at a flow rate of 200 sccm. The device power is adjusted to 80W~200W to keep the argon gas flow rate stable. The surface of the copper powder is activated for 10min~30min to increase the density of active sites on the surface of the copper powder and obtain activated copper powder.

[0053] S3. Three-stage fluidized bed CVD growth of graphene shell: Activated copper powder is fed into a three-stage fluidized bed CVD reactor, and the following three growth processes are carried out sequentially: (1) Inner layer growth: Ar gas is used as the fluidized bed carrier gas and dilution gas. The total carrier gas flow rate is maintained at 500-800 sccm. The carbon source is selected from one of ethanol, acetone, methane and ethylene. The liquid carbon source is converted into vapor by bubbling method and the gaseous carbon source is directly introduced. The process parameters are precisely controlled in three stages, as follows: (1) First stage: Low defect inner layer graphene growth reaction temperature: 550℃-600℃; carbon source type: methane gas (model: CH4-5.0, supplier: Air Liquide (Hangzhou) Co., Ltd., the same below); carbon source gas flow rate: 50-100 sccm; carbon source volume concentration: 3%-8% (carbon source volume / total gas volume in reaction chamber); reaction chamber pressure: 2000-3000 Pa; growth time: 20-30 min; in this stage, the carbon source concentration is low, the flow rate is small and the chamber pressure is relatively high, and dense low defect inner layer graphene is grown to achieve preliminary complete coating of copper core and isolate the initial oxidation of copper core.

[0054] (2) Gradient transition layer growth: The reaction temperature for graphene growth in the gradient transition layer is 500℃~550℃; the carbon source type is ethanol vapor (model: EL-UP4N, supplier: Jiangyin Kairui Chemical Technology Co., Ltd., the same below); the carbon source gas flow rate is 80~150sccm; the carbon source volume concentration is 6%~12% (carbon source volume / total gas volume in the reaction chamber); the chamber pressure is 1500~2500Pa; a small amount of water vapor or carbon dioxide (model: CO2-5.0, supplier: Air Products (China) Investment Co., Ltd., the same below) is introduced simultaneously, with a water vapor flow rate of 5~15sccm or a carbon dioxide flow rate of 3~10sccm; the growth time is 15~25min; in this stage, the carbon source flow rate and concentration are increased, the chamber pressure is reduced, and the mild etching effect of the small amount of water vapor and carbon dioxide is combined to gradually increase the graphene defect density, construct the defect gradient transition layer, and promote the stable formation of the Cu-OC composite interface transition layer.

[0055] (3) Outer layer growth: High-defect outer layer graphene growth (nitrogen doping) reaction temperature: 450℃~500℃; carbon source type: ethanol vapor; carbon source gas flow rate: 120~200sccm; carbon source volume concentration: 10%~15% (carbon source volume / total gas volume in reaction chamber); reaction chamber pressure: 1000~2000Pa; ammonia gas (model: NH3-5.0, supplier: Guangdong Huatai Gas Co., Ltd., the same below) is introduced as nitrogen source, ammonia flow rate 1~5sccm; growth time: 10~20min; at this stage, the carbon source flow rate and concentration are further increased, the chamber pressure is reduced, and a large number of polar defect sites are introduced by nitrogen doping to form high-defect outer layer graphene, which enhances the interfacial bonding force with subsequent nitrogen-containing composite resin.

[0056] S4. Cooling and Collection: After the three-stage growth is completed, Ar gas is introduced and the sample is cooled to room temperature with the furnace to obtain graphene-coated copper powder.

[0057] S5. By mass percentage, mix 85.0 wt% of graphene-coated copper powder, 1.0 wt% of sodium hypophosphite (model: SHP-EL, supplier: Zhongjuxin Technology Co., Ltd., the same below) and ascorbic acid (model: VC-E, supplier: Shijiazhuang Pharmaceutical Group Weisheng Pharmaceutical Co., Ltd., the same below) (mass ratio 1:1), and 10.0 wt% of ethylene glycol monobutyl ether (model: YD-EB, supplier: Jiangsu Yida Chemical Co., Ltd., the same below).

[0058] Sintering conditions: 200℃ / 30min.

[0059] The type of resin is the only variable used in the control experiment.

[0060] Example 1 S6.1 Weigh each component by mass percentage as follows: 85.0 wt% graphene-coated copper powder, 4.0 wt% nitrogen-containing epoxy-modified acrylic resin, 1.0 wt% sodium hypophosphite and ascorbic acid mixture, and 10.0 wt% ethylene glycol monobutyl ether. After uniformly mixing each component, sinter at a temperature of 180℃~230℃.

[0061] Example 2 S6.2 Weigh each component by mass percentage as follows: 85.0 wt% graphene-coated copper powder, 4.0 wt% pyridine-functionalized acrylic resin (model: SYNOCryl PA-Py60, supplier: Arkema (China) Investment Co., Ltd.), 1.0 wt% reducing agent, and 10.0 wt% ethylene glycol monobutyl ether. After uniformly mixing each component, sinter at a temperature of 180℃~230℃.

[0062] Example 3 S6.3 Weigh each component by mass percentage as follows: 85.0 wt% graphene-coated copper powder, 4.0 wt% amide-modified epoxy resin (model: LITE3040, supplier: Cardley Chemical (Zhuhai) Co., Ltd.), 1.0 wt% reducing agent, and 10.0 wt% ethylene glycol monobutyl ether. After uniformly mixing each component, sinter at a temperature of 180℃~230℃.

[0063] Example 4 S6.4 Weigh each component by mass percentage as follows: 85.0 wt% graphene-coated copper powder, 4.0 wt% tertiary amine modified phenolic resin (model: ZF-DMP30-818, supplier: Yueyang Zhongzhan Technology Co., Ltd.), 1.0 wt% reducing agent, and 10.0 wt% ethylene glycol monobutyl ether. After uniformly mixing each component, sinter at a temperature of 180℃~230℃.

[0064] Comparative Example 1 Ordinary copper powder (D50, distribution 0.7-0.9 μm) was used instead of graphene-coated copper powder, and the remaining components were the same as in Example 1.

[0065] Comparative Example 2 Continuous dense graphene-coated copper powder was used instead of graphene-coated copper powder, and the remaining components were the same as in Example 2.

[0066] Comparative Example 3 In this study, graphene and copper powder were physically blended to replace the graphene coating on the copper powder, and the remaining components were the same as in Example 1.

[0067] Comparative Example 4 The components were weighed according to the following mass percentages: 86 wt% graphene-coated copper powder, 4 wt% nitrogen-containing epoxy-modified acrylic resin (model: CN156NS, supplier: Sartoma (Guangzhou) Chemical Co., Ltd.), 0.3 wt% reducing agent, and 9.7 wt% ethylene glycol monobutyl ether. After the components were mixed evenly, the mixture was sintered at a temperature of 180℃~230℃.

[0068] Comparative Example 5 The components were weighed according to the following mass percentages: 72 wt% graphene-coated copper powder, 12 wt% nitrogen-containing epoxy-modified acrylic resin, 2.5 wt% reducing agent, and 13.5 wt% ethylene glycol monobutyl ether. After the components were mixed evenly, the mixture was sintered at a temperature of 180℃~230℃.

[0069] Using the conductive copper pastes of Examples 1-4 and Comparative Examples 1-5 as samples, each sample was printed on the same substrate for relevant property tests. The test process is as follows: (1) Volume resistivity The sheet resistance of the sintered conductive film was measured using a four-probe tester, and the volume resistivity was calculated based on the film thickness: ρ=R s ×d In the formula: ρ is the volume resistivity (Ω·cm), R s d is the sheet resistance (Ω / □) and d is the film thickness (cm).

[0070] (2) Stability during high temperature and high humidity aging The sample was aged in an environment of 85℃ and 85% relative humidity for 500 hours. The resistivity before and after aging was measured, and the drift rate was calculated. Resistivity drift (%) = |(Resistivity after aging - Resistivity before aging)| / Resistivity before aging × 100% (3) Adhesion Using the 100-grid cross-cutting method, a 1mm × 1mm grid is drawn with a cross-cutting tool, and 3M tape is quickly torn off. According to ASTM D3359 rating, 5B is the best, with no peeling; the rating decreases accordingly.

[0071] (4) Improved antioxidant performance Thermogravimetric analysis (TGA) was used to determine the oxidation initiation temperature, and the improvement in antioxidant capacity was evaluated by comparing it with that of ordinary copper powder.

[0072] The test results of the examples and comparative examples are shown in Table 1.

[0073] Table 1 Test results of the examples and comparative examples

[0074] As can be seen from Table 1, the volume resistivity of the low-temperature sintered conductive copper pastes provided in Examples 1-4 is all above 10. -6The resistivity is on the order of Ω·cm, while that of comparative examples 1–3 is all in the range of 10. -5 The result is on the order of Ω·cm, indicating that graphene-coated copper powder can significantly improve conductivity.

[0075] The low-temperature sintered conductive copper pastes provided in Examples 1-4, after aging for 500 hours at 85°C / 85%RH, all showed a resistivity drift rate of less than 3.0%, while the drift rates of Comparative Examples 2 and 3 were 12.5% ​​and 18.3%, respectively, and Comparative Example 1 even failed, indicating that the material of the present invention has better stability under harsh environments.

[0076] The adhesion of the low-temperature sintered conductive copper pastes provided in Examples 1-4 all reached the highest level of 5B, while the highest level in the comparative examples was only 4B. This shows that the present invention has a better bonding force between the coating and the substrate and has obvious advantages.

[0077] In Examples 1-4, the oxidation initiation temperature was increased by more than 110°C compared to ordinary copper powder, reaching a maximum of 120°C, while the increase in Comparative Examples 2 and 3 was only 40°C and 30°C, respectively. This demonstrates that the graphene-coated copper powder structure effectively delays the oxidation of copper powder.

[0078] As can be seen, the low-temperature sintered conductive copper pastes of Examples 1-4 are significantly superior to the comparative examples in terms of conductivity, stability, adhesion, and oxidation resistance. The reason for this is that the nitrogen-containing composite resin described in this invention is the core functional component of the copper paste system. The nitrogen atom active sites in its molecular structure can form stable coordination bonds and hydrogen bonds with the hydroxyl and carboxyl groups on the outer layer of the graphene shell, significantly improving the dispersibility of graphene-coated copper powder in the organic system and inhibiting particle agglomeration. Simultaneously, the resin can fully melt and level during low-temperature sintering, increasing the film density, and leaving no residual impurities after decomposition, ensuring the continuity and integrity of the conductive network. Furthermore, the nitrogen-containing composite resin can form a strong interfacial bond with the flexible substrate, greatly improving the film adhesion.

[0079] As can be seen from the performance comparison data of the examples and comparative examples in Table 1, under the premise that the type of copper powder, particle size, additives, solvents and sintering conditions are completely uniform, the performance can be precisely controlled by simply changing the type of nitrogen-containing composite resin.

[0080] Example 1 uses a nitrogen-containing epoxy-modified acrylic resin with the strongest coordination ability, the best low-temperature compatibility, and no residue after decomposition, which makes the copper powder most uniformly dispersed and has the highest sintering density, resulting in the lowest resistivity and the best weather resistance. The amide-modified epoxy resin in Example 3 has a slightly lower coordination ability and its performance is slightly weaker than that in Example 1. Due to differences in the number and structure of active sites, the pyridine-functionalized acrylic resin of Example 2 and the tertiary amine-modified phenolic resin of Example 4 exhibited further reduced dispersion and interfacial bonding, while resistivity and aging drift rate increased slightly.

[0081] Compared with Examples 1 and 3, and compared with the comparative examples using ordinary copper powder, dense graphene-coated copper powder, and physical blending of graphene and copper powder, the present invention achieves comprehensive and significant improvements in conductivity, damp heat reliability, adhesion, and oxidation resistance through the graphene shell-core-shell structure and dual-interface synergistic system. The overall performance is significantly superior to existing technical solutions. Comparative Example 4 uses a high copper powder content and a low resin and reducing agent ratio. Although the proportion of graphene-coated copper powder is high, the resin content is too low to form a complete interface coating, and the reducing agent is insufficient to achieve effective self-reduction. This results in poor copper powder dispersion, discontinuous conductive network after sintering, and no antioxidant protection. It fails directly after high temperature and high humidity aging, with a significant increase in volume resistivity and an adhesion of only 3B grade, with no antioxidant improvement effect.

[0082] Comparative Example 5 uses a low copper powder content, a high resin and a high-low reducing agent ratio. The resin and reducing agent are in excess. On the one hand, the excess resin greatly increases the interfacial impedance, blocking the conductive path formed by the copper powder and graphene, resulting in an increase in volume resistivity. On the other hand, the excess resin reduces the film density, making it easy to absorb moisture in a humid and hot environment, which causes an increase in resistivity drift. At the same time, the high resin content will accelerate the oxidation of the copper powder interface due to moisture absorption. Therefore, the anti-oxidation improvement temperature is only ≥40℃, which is much lower than that of Example 1.

[0083] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the appended claims.

Claims

1. A low-temperature sintered conductive copper paste, characterized in that, include: Graphene-coated copper powder, nitrogen-containing composite resin, reducing agent, and organic solvent; The graphene-coated copper powder includes a copper core and a graphene shell covering the copper core, wherein the defect density of the graphene shell increases from the inside to the outside. The graphene shell comprises a low-defect inner layer of graphene and a high-defect outer layer of graphene containing defective active sites.

2. The low-temperature sintering conductive copper paste as described in claim 1, characterized in that, The graphene-coated copper powder comprises 72wt% to 86wt% by weight, the nitrogen-containing composite resin comprises 4wt% to 12wt%, the reducing agent comprises 0.3wt% to 2.5wt%, and the organic solvent comprises the remainder.

3. The low-temperature sintering conductive copper paste as described in claim 1, characterized in that: The graphene shell also includes a gradient transition layer of graphene, and the low-defect inner graphene, the gradient transition layer of graphene, and the high-defect outer graphene are sequentially coated on the copper core.

4. The low-temperature sintering conductive copper paste as described in claim 1, characterized in that: The defective active sites include polar active groups.

5. The low-temperature sintering conductive copper paste as described in claim 3, characterized in that: The diameter of the copper core ranges from 0.7 to 0.9 μm, and the median diameter is 0.8 μm; and / or, the sum of the thicknesses of the low-defect inner graphene layer, the gradient transition layer graphene, and the high-defect outer graphene layer is 0.8 nm to 3.5 nm; and / or, the coverage of the copper core by the graphene shell is 92% to 98%.

6. The low-temperature sintering conductive copper paste as described in claim 1, characterized in that: The nitrogen-containing composite resin is selected from one or more of the following: nitrogen-containing epoxy-modified acrylic resin, amide-modified epoxy resin, pyridine-functionalized acrylic resin, tertiary amine-modified phenolic resin, polyamide-imide-modified epoxy resin, and nitrogen-doped polyurethane resin.

7. The low-temperature sintering conductive copper paste as described in claim 1, characterized in that: The organic solvent includes one or more of the following: terpineol, ethylene glycol monobutyl ether, diethylene glycol monobutyl ether, diethylene glycol ethyl ether acetate, ethylene glycol monobutyl ether acetate, propylene glycol methyl ether acetate, dipropylene glycol methyl ether, tributyl citrate, and dioctyl adipate. And / or, the reducing agent comprises two or more of hypophosphite, ascorbic acid derivatives, polyols, and organic amines.

8. A method for preparing a low-temperature sintered conductive copper paste, characterized in that, include: Graphene-coated copper powder was prepared using a three-stage low-temperature fluidized bed chemical vapor deposition process. The three-stage low-temperature fluidized bed chemical vapor deposition process includes a first stage, a second stage, and a third stage; In the first stage, low-defect inner-layer graphene was grown at 550℃~600℃. In the second stage, a gradient transition layer of graphene was grown at 500℃ to 550℃. In the third stage, high-defect outer layer graphene is grown by nitrogen doping at 450℃~500℃.

9. The preparation method according to claim 8, characterized in that, The first stage also includes: low concentration carbon source, Ar / H2 atmosphere, growth for 5 min to 15 min, forming low defect inner layer graphene; The second stage also includes: increasing the carbon source concentration, introducing trace amounts of water vapor or CO2, growing for 3 to 8 minutes, gradually increasing the defect density, and forming a gradient transition layer of graphene. The third stage also includes: a high-concentration carbon source, a trace amount of NH3 atmosphere, growth for 5 min to 12 min, to form a high-defect outer layer of graphene rich in pyridine nitrogen, hydroxyl groups, and carboxyl groups.

10. An electronic device, characterized in that, The invention includes a flexible substrate coated with a flexible film layer, wherein the flexible film layer is formed by sintering the low-temperature sintered conductive copper paste as described in any one of claims 1-7, or by sintering the low-temperature sintered conductive copper paste prepared by the method described in claim 8 or 9.

11. The electronic device as claimed in claim 10, characterized in that: The volume resistivity of the flexible film layer is ≤6.5×10⁻⁶. -6 Ω·cm, resistivity drift rate <3% after aging at 85℃ and 85% relative humidity for 500h.

Citation Information

Patent Citations

  • Preparation method of antioxidant high-conductivity graphene-copper composite powder

    CN117680676A

  • Micro-nano silver powder with controllable particle size and preparation method thereof

    CN120190346A